Implementasi Kebijakan Revitalisasi Industri Gula Sebagai Upaya Mencapai Swasembada Komoditas Gula (Studi Pada PT Perkebunan Nusantara XI Pabrik Gula Pagotan) - Susanti, Lilis (Jurnal Administrasi Publik, 2015)
Abstract: Policy Implementation Of Sugar Industry Revitalization As Efforts To Achieve Self-Sufficiency In Sugar Commodity (Implementation Study On The Sugar Factory PTPN XI Pagotan). In the Science of Public Administration has traditionally practice includes two things: public service and public policy. Furthermore, the public policy set many problems one of which related to the issues of food that is sugar. Sugar is one of the basic needs whose needs are always increasing every year. Therefore, the government issued a sugar self-sufficiency program in household consumption (GKP) and the consumption of sugar production (RCC) in 2014. In the self-sufficiency program, namely the national sugar production target of 5.7 million tonnes of sugar GKP consisting of $ 2.96 million ton and sugar GKR of 2.74 million tons. To achieve the program, the government issued a policy of revitalization of the sugar industry through the Minister of Industry Number 11 / M-IND / PER / 1/2010 About Maps Guide (Road Map) Sugar Industry Cluster Development. In this case the sugar factory PTPN XI Pagotan is one of the sugar mills that use these rules as guidelines for policy to do the development in the sugar factory. The results showed that the sugar industry revitalization policies implemented by the sugar factory PTPN XI Pagotan are in accordance with Permenperin No. 11 of 2010. The action plan is implemented include improved performance on-farm, off-farm, human resource development and enhancement of partnerships have also been carried out. But when seen through the results of its performance indicators productivity of sugar in the plant pagotan still lacking support sugar self-sufficiency program in 2014. Productivity PG Pagotan decreased from 2010-2014 and not suitable with the target that was plan in RKAP document. It has  impact on the national sugar production in 2014 that was only 2.57 million tonnes and doesn’t reach the target of self-sufficiency especially in sugar GKP amounted till 2.96 million tons. Exacrly, that was need more effort through hard work according to the revitalization policy that was formulated by the stakeholders. Keywords: public policy, policy implementation, sugar self-suffiency 2014   Abstrak: Implementasi Kebijakan Revitalisasi Industri Gula Sebagai Upaya Mencapai Swasembada Komoditas Gula (Studi Pada PT Perkebunan Nusantara XI Pabrik Gula Pagotan). Ilmu Administrasi Publik praktiknya meliputi dua yaitu pelayanan publik dan kebijakan publik. Kebijakan publik mengatur permasalahan salah satunya yaitu gula. Gula merupakan kebutuhan pokok yang kebutuhannya selalu bertambah. Oleh karena itu pemerintah mengeluarkan program swasembada gula tahun 2014. Dalam swasembada tersebut target produksi gula nasional yaitu sebesar 5,7 juta ton yang terdiri dari GKP sebesar 2,96 juta ton dan GKR sebesar 2,74 juta ton. Pemerintah mengeluarkan kebijakan revitalisasi industri gula melalui Peraturan Menteri Perindustrian Nomor 11/M-IND/PER/1/2010 Tentang Peta Panduan (Road Map) Pengembangan Klaster Industri Gula. PTPN XI Pabrik Gula Pagotan mengimplementasikan peraturan tersebut. Hasil penelitian ini yaitu kebijakan revitalisasi industri gula yang dilaksanakan oleh PTPN XI Pabrik Gula Pagotan sudah cukup konsisten. Program yang diimplementasikan yaitu peningkatan kinerja on farm, off farm, pengembangan SDM dan peningkatan kemitraan. Hasil kinerja pabrik gula Pagotan yaitu masih cenderung menurun dan kurang mendukung swasembada gula di tahun 2014. Hal tersebut berdampak pada produksi gula tahun 2014 hanya 2,57 juta ton dan tidak memenuhi target swasembada gula GKP sebesar 2,96 juta ton.   Kata kunci: kebijakan publik, implementasi kebijakan, swasembada gula 2014